Stabilization of stochastic complex networks with delays based on completely aperiodically intermittent control. (November 2021) - Zhai, Ying; Wang, Pengfei; Su, Huan
Abstract: This paper investigates the stabilization problem of stochastic complex networks with delays via completely aperiodically intermittent control. Superior to most existing results based on aperiodically intermittent control strategy that can only satisfy quasi periodicity, our proposed control scheme can render the lower bound of certain control intervals to be arbitrarily small, the upper bound of certain control periods to be very large and the proportion of rest intervals to be any value in (0, 1). Thus, the constraints are loosened and the conservativeness is reduced compared with the existing related results. This is accomplished by presenting novel concepts, that is, average control rate and average control period. Under the designed controller, the studied networks are stable with small time delays and large time delays, respectively. Finally, the simulation results are provided to verify the effectiveness of the proposed control scheme.